The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1980-57642015dn93000012
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions as a potential neurocognitive endophenotype in anxiety disorders: A systematic review considering DSM-IV and DSM-5 diagnostic criteria classification

Abstract: Evidence in the literature indicates that neurocognitive impairments may represent endophenotypes in psychiatric disorders.ObjectiveThis study aimed to conduct a systematic review on executive functions as a potential neurocognitive endophenotype in anxiety disorder diagnosis according to the DSM-IV and DSM-5 classifications.MethodsA literature search of the LILACS, Cochrane Library, Index Psi Periódicos Técnico-Científicos, PubMed and PsycInfo databases was conducted, with no time limits. Of the 259 studies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Responding to the identified need for well‐powered OCD neurocognitive endophenotype studies (e.g., Muller et al, ), this is the first study comparing pediatric OCD, genetically at‐risk sibling, and HC groups. Examining potential risk markers of pediatric OCD, a subtype of the disorder with inflated genetic influence compared to its adult‐onset form, the study aligns with ENIGMA recommendations to aim for understanding of precise mechanisms underlying abnormalities that both precede OCD onset and that present during the course of OCD (Boedhoe et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responding to the identified need for well‐powered OCD neurocognitive endophenotype studies (e.g., Muller et al, ), this is the first study comparing pediatric OCD, genetically at‐risk sibling, and HC groups. Examining potential risk markers of pediatric OCD, a subtype of the disorder with inflated genetic influence compared to its adult‐onset form, the study aligns with ENIGMA recommendations to aim for understanding of precise mechanisms underlying abnormalities that both precede OCD onset and that present during the course of OCD (Boedhoe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, zero pediatric studies and 12 adult studies have assessed neurocognition in unaffected first‐degree relatives of those with OCD (Table ). Findings across these adult studies have been inconsistent due to differences in examined neurocognitive subdomains (Muller et al, ). All OCD endophenotype studies enrolled adults primarily with aOCD.…”
Section: Introductionmentioning
confidence: 99%
“…Lysaker et al (2005) reported that, in schizophrenia, trait anxiety is associated with impairments in neurocognitive functions (Lysaker et al, 2005). Impairments in set-shifting, cognitive flexibility, planning and response inhibition are frequently detected in disorders with an anxious phenotype (Muller et al, 2015).…”
Section: Affective Symptoms Are Strongly Associated With the Cognitommentioning
confidence: 99%